2017
DOI: 10.1080/07388551.2016.1260525
|View full text |Cite
|
Sign up to set email alerts
|

Genoproteomics-assisted improvement ofAndrographis paniculata: toward a promising molecular and conventional breeding platform for autogamous plants affecting the pharmaceutical industry

Abstract: Andrographis paniculata (Burm. f.) Wall. ex Nees. (AP) is a hermaphroditic, self-compatible, and habitual inbreeding plant. Its main bioactive component is andrographolide, which is capable of inducing autophagic cell death in some human cancer cells and helps fight HIV/AIDS. Increasing the andrographolide content by investigating the genetic mechanisms controlling its biosynthesis in order to improve and develop high-yielding cultivars are the main breeding targets for AP. However, there might exist some limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Structural analysis of andrographolide derivatives showed that various enzymatic reactions occur during biotransformation such as enzymatic hydrolyzation, hydroxylation, oxidation, glycosylation, epoxidation, and elimination (Wang et al 2011). A. paniculata leaf contains proteins 1,144 mg/g (Valdiani et al 2017) and alkaloid (Harmine), an indole alkaloid in the Carboline group (Kurzawa et al 2015) which is easily bound with other compounds and synthesized in a newly formed derivative molecular structure (Laine et al 2014).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…Structural analysis of andrographolide derivatives showed that various enzymatic reactions occur during biotransformation such as enzymatic hydrolyzation, hydroxylation, oxidation, glycosylation, epoxidation, and elimination (Wang et al 2011). A. paniculata leaf contains proteins 1,144 mg/g (Valdiani et al 2017) and alkaloid (Harmine), an indole alkaloid in the Carboline group (Kurzawa et al 2015) which is easily bound with other compounds and synthesized in a newly formed derivative molecular structure (Laine et al 2014).…”
Section: Lc-ms/ms Analysismentioning
confidence: 99%
“…The genomic and breeding aspects of roselle plant should be taken into further consideration in future. Reportedly, a similar trend in Malaysia, including marker development (Valdiani et al 2013) and intra-specific hybridization (Valdiani et al 2012), has led to developing functional breeding platforms for medicinal plants such as Andrographis paniculata (Valdiani et al 2017).…”
Section: Flavanone 3-hydroxylase Transcript (Hsf3h) Of Hibiscus Sabdariffa Lmentioning
confidence: 99%
“…Improved nutrient content and WP can be accomplished by breeding water/nutrient -efficient crops. The International Center for Agricultural Research in the Dry Areas (ICARDA) along with internationally recognized academic breeding centers has established a solid platform for WP breeding (Dwivedi, Britt et al 2015;Ortiz 2015;Lobos, Camargo et al 2017;Valdiani, Talei et al 2017). Selected genotypes are better suited to cope with environmental fluctuations and extremes such as drought and heat spells.…”
Section: Introductionmentioning
confidence: 99%
“…Selected genotypes are better suited to cope with environmental fluctuations and extremes such as drought and heat spells. Whole-genome prediction models estimate all marker effects in all loci and capture small quantitative trait loci (QTL) mapping effects are applied have resulted in impressive advances and became routine in agricultural breeding (Dwivedi, Britt et al 2015;Ortiz 2015;Lobos, Camargo et al 2017;Valdiani, Talei et al 2017). At the phenotype level, improved agricultural techniques and novel highthroughput selection systems are being developed to enable rapid pre-field screening for specific traits.…”
Section: Introductionmentioning
confidence: 99%